2014
DOI: 10.1186/s12967-014-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow derived mesenchymal stromal cell therapy in combination with everolimus to preserve renal structure and function in renal transplant recipients

Abstract: BackgroundKidney transplantation has improved survival and quality of life for patients with end-stage renal disease. Despite excellent short-term results due to better and more potent immunosuppressive drugs, long-term survival of transplanted kidneys has not improved accordingly in the last decades. Consequently there is a strong interest in immunosuppressive regimens that maintain efficacy for the prevention of rejection, whilst preserving renal structure and function. In this respect the infusion of mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 72 publications
0
44
0
Order By: Relevance
“…Systemic immunosuppression by bone marrow MSCs (1 million/kg) has been indicated in kidney allograft transplant patients for the possible improvement of rejection and fibrosis in donor organs (Reinders et al, 2013(Reinders et al, , 2014. Graft versus host disease (GVHD) is a serious consequence of the host immune system recognizing and rejecting allogeneic grafts.…”
Section: Mscsmentioning
confidence: 99%
“…Systemic immunosuppression by bone marrow MSCs (1 million/kg) has been indicated in kidney allograft transplant patients for the possible improvement of rejection and fibrosis in donor organs (Reinders et al, 2013(Reinders et al, , 2014. Graft versus host disease (GVHD) is a serious consequence of the host immune system recognizing and rejecting allogeneic grafts.…”
Section: Mscsmentioning
confidence: 99%
“…Endogenous autologous stem cells have also been shown to participate in injury repair and regeneration in many experimental (4)(5)(6) and clinical scenarios (7)(8)(9)(10), and some have compared the two sources of stem cells for relative clinical efficacy (11). In addition, investigators have shown an immunomodulatory effect of stem cells (12)(13)(14) and suggested a role as therapeutic adjunct after transplantation (15)(16)(17). Our researchers previously demonstrated that a Lewis-to-DA rat liver graft becomes a host-donor chimera via recipient stem cell repopulation and is accepted without immunosuppression (18).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, rationale for use of MSCs in renal recipients includes a reduction in severity of IRI, prevention and reversal of acute transplant rejection, and reversal or stabilization of chronic transplant inflammation and fibrosis. In addition, adding MSCs to the immune suppressive regimen might facilitate CNI withdrawal with the aim of preserving renal function and structure [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%